Improving the Concept Understanding of Mixed Fractions Calculation Operations Using the Jigsaw Method Assisted by Trimino Media - Eliza Dwi Cahyanti; Nurafni (Universitas Pendidikan Ganesha, 2024)
This research is to analyze the significant influence of understanding the material concept of calculating mixed fraction operations using the Jigsaw method assisted by Trimino media. This research uses a nonequivalent control group design and quantitative quasi-experimental methodology. Participants in this research were all 50 class IV students from two classes. Simple random sampling was used for the sampling process, and obtained 25 students as a class who were given treatment in the form of the Jigsaw method with trimino media, and 25 students as a class who were given treatment in the form of the conventional method. Pretest and posttest worksheets with essay questions are the testing format used in this research. The test was carried out twice, once before and once after. Meetings were held eight times for this research: once for the pretest, six times for the Jigsaw technique using trimino media, and once for the posttest. The instrumentation of this research consists of tests, observations, and documentation. The t-test, which had previously been tested for homogeneity and normality, was used in the data analysis procedure. The results of the research show that there is a significant influence on students' conceptual understanding in classes that apply the Jigsaw method assisted by Trimino media, with a significance level of 5%. The t-test hypothesis test shows that H0 is rejected and H1 is accepted if t-count (6.211) > t-table (2.011). This shows that the use of the Jigsaw method assisted by Trimino media in solving mathematical problems has a good influence on the knowledge of class IV students in the material of understanding mixed fraction calculation operations.